THE PRELIMINARY RESEARCH FOR IMPLEMENTATION OF IMPROVED DTC SCHEME OF HIGH PERFORMANCE PMSM DRIVES BASED ON FPGA - Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2008)
The direct torque control (DTC) is one of control approache that is used commonly in PMSM control system. This method supports a very quick and precise torque response. However, the DTC method is not perfect and has some disadvantages. Many researchers have been proposed to modify the basic DTC scheme for PMSM drive. All this contributions allow performance to be improved, but at the same time they lead to more complex schemes. Furthermore, the PMSM drive control systems are usually based on microcontroller and DSP. Some researchers also have been used DSP and FPGA together to develop DTC for AC drives. These allow improving the performance, but they will increase cost. For the reason above, this paper proposed a new DTC scheme to apply only based on FPGA. The preliminary research showed that the proposed DTC sheme can reduce torque and flux ripples significantly. Therefore, this paper also recomend to realize proposed DTC scheme based on FPGA in order to support to execute very fast computation.The implementation is hoped that it will very potential to replace not only the induction motor but also the DC servo motor in a number of industrial process, commercial, domestic and modern military applications of high-performance drive.